Analyzing Flood Disaster Risks in Senior High School: Envidence from Surakarta, Indonesia - Ajeng Santika Putri; Yunus Aris Wibowo; Ratih Puspita Dewi (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Flood disasters represent one of the most critical environmental challenges in Surakarta, particularly in areas along the Bengawan Solo River watershed, where high rainfall intensity and rapid land use changes substantially increase inundation risk. Educational facilities, especially Senior High Schools, are vulnerable due to their spatial distribution, physical conditions, and population characteristics. This study aims to analyze flood hazard, vulnerability, and risk levels of Senior High Schools in Surakarta as a scientific basis for strengthening disaster preparedness and risk reduction within school environments. Methodology: This research employed a quantitative approach supported by spatial analysis. Flood hazard mapping was conducted using the Weighted Sum Method by integrating elevation, slope, rainfall, land use, and river proximity parameters. Vulnerability assessment was performed using physical and social indicators, including building condition, drainage, accessibility, population exposure, and institutional capacity, derived from secondary data and field surveys. Flood risk levels were identified through the integration of hazard and vulnerability components.Results: The results indicate that flood hazard areas in Surakarta are dominated by high and moderate classes, particularly in Serengan, Pasar Kliwon, and parts of Jebres District. Vulnerability analysis shows that fifty seven schools have high physical vulnerability and sixty six schools exhibit high social vulnerability. Combined vulnerability classification identifies fifty seven schools as high, twenty seven as medium, and one as low. Flood risk analysis indicates that fifty one schools fall into the high risk category.Applications/Originality/Value: This study provides an assessment of flood risk in educational facilities and supports School Based Disaster Preparedness Programs to enhance resilience.